ANALISIS DETERMINAN PENYERAPAN TENAGA KERJA UMKM DI INDONESIA - Nasution, Diwayana Putri; Faried, Annisa Ilmi; Agustino, Aldi (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This study aims to analyze the improvement of the MSME sector to the absorption of labor in Indonesia. This study uses secondary data and time series data from 2004 to 2018. The data analysis model in this study uses simultaneous equation model with TSLS method. The results of the first equation study showed there are two variables for simultaneous results that show GDP negatively and significantly affects the absorption of labor and the number of MSMEs has a positive and significant effect on the absorption of labor. The second equation shows the minimum wage has a positive and significant effect on unemployment and the population has a negative and significant effect on unemployment.